A Self-led Self-management Intervention Supporting Teens with IBD (ASSIST-IBD): protocol for a feasibility study of a novel digital treatment adherence intervention - Rafeeq Muhammed; Rachel Shaw; Gemma Heath; Lou Atkinson; Cassandra Screti (BMJ Open)
Introduction Treatment non-adherence is common in young people with inflammatory bowel disease (IBD), yet support is lacking. A self-led self-management intervention supporting teens with IBD (ASSIST-IBD) is a new theory-based digital treatment adherence intervention, co-developed by young people living with IBD. ASSIST-IBD includes 10 short modules supporting adolescents to feel confident to follow their treatment plan, develop skills to overcome adherence obstacles, feel confident when talking to others about IBD and feel positive about the future. This research aims to determine the feasibility of implementing and measuring the effectiveness of ASSIST-IBD, using a single-arm mixed-methods feasibility trial.Methods and analysis 24 young people (aged 13–17) with IBD identified as being ≤80% adherent, and their parents, will use ASSIST-IBD for 6–12 weeks. For the primary endpoint of progression to randomised controlled trial, qualitative and quantitative data will be collected on; number of eligible members of the target population; number of recruited participants; reasons for non-participation and ineligibility; retention and follow-up rates; reasons for early withdrawal; completeness and utility of outcome measures; as well as further data on intervention acceptability, user experiences and user engagement. Secondary outcomes of preliminary effectiveness will include pre-intervention and post-intervention measures of treatment adherence (MARS-5), quality-of-life (IMPACT-III) and well-being (WEMWBS), and self-reported behaviour change success. Quantitative data will be analysed using descriptive statistics; qualitative data will be analysed thematically. An active patient and public involvement and engagement group will advise on the research throughout, including the development of the protocol.Ethics and dissemination The study has been granted ethical approval by Aston University’s Health and Life Sciences Research Ethics Committee (ref:#HLS2112) and NHS Research Ethics Committee, Nottingham 1 Board (IRAS:#344918). Findings will be disseminated via peer-reviewed publications and lay summaries.Registration details This protocol is registered on the Open Science Framework (https://doi.org/10.17605/OSF.IO/KC649).